2018
DOI: 10.21608/eajbsd.2018.29180
|View full text |Cite
|
Sign up to set email alerts
|

Histological, Histochemical and Ultrastructure Studies on the Ostrich Pancreas (Struthio camelus)

Abstract: Journal is an Egyptain journal covering the whole field of general, experimental, systematic and applied entomology. Manuscripts generally should not exceed 30 pages (exceptions are possible, particularly in case of reviews, and should be negotiated in advance with the editors). Papers are considered by referees before acceptance. Authors will receive first editorial decision within 8 weeks from confirmed submission. All contributions are published in English. Authors whose mother tongue is not English are str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 19 publications
7
4
0
Order By: Relevance
“…Moreover, This result is in line with Mikami et al (1985) in Japanese quail, but differs in the shape of the alpha cells, they stated the alpha cells had a columnar shape. The result in the present study of beta cells is in line with the result of Helmy and Soliman (2018) in ostrich.The observation of delta cells in this study is in line with Al-Shaeli ( 2010) in duck pancreas, Furthermore, some researchers recorded that delta cells were not found in pancreatic islets of some birds such as Stornelli et al (2006) in ostrich and Mobini (2011) in goose.…”
Section: The Pancreatic Islet Cellssupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, This result is in line with Mikami et al (1985) in Japanese quail, but differs in the shape of the alpha cells, they stated the alpha cells had a columnar shape. The result in the present study of beta cells is in line with the result of Helmy and Soliman (2018) in ostrich.The observation of delta cells in this study is in line with Al-Shaeli ( 2010) in duck pancreas, Furthermore, some researchers recorded that delta cells were not found in pancreatic islets of some birds such as Stornelli et al (2006) in ostrich and Mobini (2011) in goose.…”
Section: The Pancreatic Islet Cellssupporting
confidence: 91%
“…The microscopicscanning of the duck pancreas revealed that pancreatic islets were found in three types alpha, beta, and mixed islets(Figure 2). This result agrees with in quails, Simsek et al (2009) in the Falcon, Al-Shaeli (2010) in duck, and Helmy and Soliman (2018) in ostrich. Moreover, this result is in contrast with Al-Agele and Mohammed (2012) on golden eagle and Jaafar (2019) in Falcon, those researchers reported the islets are found in two types of darks and light islets in these birds.…”
Section: The Structure Of Pancreatic Isletssupporting
confidence: 91%
“…Accordingly, the alpha islets are primarily composed of moderately stained alpha cells and several weakly stained beta cells. The beta islets mildly stained with TB dye is densely packed with beta cells and sparsely packed with alpha and delta cells (1). The use of the toluidine blue stain in this study demonstrates that Langerhans islets are negative in all cells to save the Beta cells, which exhibit a weak reactivity with toluidine blue (light pink), while the secretory units are negative.…”
Section: Discussionmentioning
confidence: 55%
“…In the digestive system, the pancreas is a key glandular organ. The initial investigations establish that most bird species have three distinct pancreatic cell types (A, B, and D cells) (1). In addition, some previous studies report that the avian pancreas is separated from the right side of the abdominal cavity in all birds.…”
Section: Introductionmentioning
confidence: 97%
“…The splenic lobe also is not persistent. For example, this lobe is absent in mynah (Saadatfar & Asadian, 2009), ostrich (Helmy & Soliman, 2018), Bulbul (Al‐Khakani et al, 2019), and Kestrel (Al‐Haaik, 2019; Palmieri & Shivaprasad, 2014). However, the splenic lobe is reported in falcon (Simsek et al, 2009), and golden eagle (Al‐agele & Mohammed, 2012), as captive birds.…”
Section: Discussionmentioning
confidence: 99%